Rural development strategies of NGOs - Rajasekhar, D. (1998)
In the contemporary NGO discussions, the issue of accountability (i.e., to what extent NGOs strive to achieve the objectives that they set for themselves) is often highlighted. Based on the primary data collected from sixteen rural development NGOs in Karnataka, this paper examines the objectives that the NGOs formulated and activities pursued to analyse the question of their accountability to the people that they work with. The paper argues that there is a mis-match between the objectives and activities and that NGO strategies evolve not on the basis of people's needs and aspirations, but on the basis of donor considerations. - Reproduced
Keywords: Nongovernmental organizations - India; Rural development - India; Rural development